Identification of Causal Factors of Peel-Pulp Splitting and Peeling Difficulty Disorders in ‘Mas’ Banana [Musa Sapientum Cv. Mas (Aa)] - Wo, Soek Meng (2007)
‘Mas’ banana is among the most favoured of all the local dessert bananas because of its fascinating golden peel and light orange, aromatic and sweet pulp. However, this dessert cultivar was found to be susceptible to peel-pulp splitting disorder (PPSD) and peeling difficulty disorders (PDD). Thus, study was conducted to identify the causal factors of PPSD and PDD of Mas banana during fruit development and ripening, respectively. Incidence of PPSD and the physical characteristics of the fruits were determined at harvest dates of 4, 5, 6, 7, 8 and 9 weeks after flower emergence (WAFE) for three fruiting seasons (FS1, FS2 and FS3). Chemical characteristics and nutrient contents in PPSD and normal fruits harvested at 6, 7, 8 and 9 WAFE were determined. The anatomical characteristics of the PPSD and normal fruits were also studied. Incidence of PPSD was found to be the most severe at FS3 which was a rainy season after a drought season. Incidence of PPSD was significantly (P≤0.05) and positively correlated to fruit circumference, pulp weight and pulp to peel ratio. This suggested that the increase in fruit splitting was related to a rapid increase in fruit size. Significant (P≤0.05) increases in pulp moisture content and significantly (P≤0.05) higher peel moisture content of PPSD fruits suggested that rapid increase in pulp volume had put stress on the peel and caused the fruit to split. Significantly lower peel calcium in PPSD fruits also suggested that PPSD was a Ca-deficiency disorder which had caused a lower cell wall turgidity and intercellular strength in the fruits. Results obtained for soluble solids concentration, titratable acidity and pH of the fruits indicated that the fruits had achieved harvest maturity at 6 to 7 WAFE. As shown in the scanning electron micrographs (SEM), the intercellular space of PPSD fruits had been fully occupied due to the rapid cell expansion, imposing stress on the peel which rendered the fruit to split. Occurrence of PDD was determined on fruits ripened at three levels of RH (high – 90 ± 5%, medium – 70 ± 5 %, low – 50 ± 5 %) during 5 to 8 ripening days. The corresponding quality and anatomical characteristics of the fruits in relation to PDD were also determined. Fruits ripened at low and medium RH conditions manifested PDD. There was an advanced ripening in fruits ripened at low RH as compared to fruits ripened at medium and high RH. This was shown by the significant (P≤0.05) linear and quadratic relationships between peel colour (L* and C*) and ripening day. Occurrence of PDD was significantly (P≤0.05) and positively correlated to weight loss and sugar: acid, but was negatively correlated to peel thickness and peel moisture content. These indicated that PDD increased with an increase in moisture loss when ripened at RH lower than 70%. SEM showed that severe water loss in fruits caused the cells to contract and loss turgor, resulting in loss of cell wall turgidity and reduced intercellular spaces. Thus, peelpulp transition layer was not readily separated from the outermost layer of the pulp because of absence of intercellular spaces to facilitate peeling.